Schistosoma japonicum SjE16.7 Protein Promotes Tumor Development via the Receptor for Advanced Glycation End Products (RAGE) - Wu, Chenyun; Du, Xinyue; Tang, Lili; Wu, Jianhua; Zhao, Wei; Guo, Xiaokui; Liu, Dengyu; Hu, Wei; Helmby, Helena; Chen, Guangjie; Wang, Zhaojun (Frontiers in Immunology, 2020)
Schistosome infection contributes to cancer development, but the mechanisms are still not well understood. SjE16.7 is an EF-hand calcium-binding protein secreted from Schistosoma japonicum eggs. It is a neutrophil attractant and macrophage activator, and as such plays an important role in the inflammatory granuloma response in schistosomiasis. Here we show that SjE16.7 bind to host cells by interacting with receptors for advanced glycation end-products (RAGE). This ligation leads to activation of the NF-kB signaling pathway, an increase in the generation of reactive oxygen species, and production of the pro-inflammatory cytokines IL-6 and TNF-a. Using a mouse model of colorectal cancer we demonstrate that intraperitoneal injection of SjE16.7 promotes colorectal cancer progression along with systemic myeloid cell accumulation. Thus, our results identify a new helminth antigen contributing to tumor development in the mammalian host.